2018
DOI: 10.1186/s12889-018-6165-3
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of small-area-based socioeconomic characteristics in assessing the treatment outcomes of type 2 diabetes patients: a register-based mixed-effect study

Abstract: BackgroundAssessment of the differences in the outcomes of care by socioeconomic status (SES) is beneficial for both the efficient targeting of health care services and to decrease health inequalities. This study compares the effects of three patient-based SES predictors (earned income, educational attainment, employment status) with three small-area-based SES predictors (median income, educational attainment, proportion of the unemployed) on the treatment outcomes of type 2 diabetes patients.MethodsMixed-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…We observed that lower individual‐level education increased the mean levels of HbA 1c by 1.9% (95% CI 1.1, 2.8), independently of sex, age group, other individual‐level SES variables and area‐level deprivation (social and material), which is in agreement with the few previous works 13,17,18 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We observed that lower individual‐level education increased the mean levels of HbA 1c by 1.9% (95% CI 1.1, 2.8), independently of sex, age group, other individual‐level SES variables and area‐level deprivation (social and material), which is in agreement with the few previous works 13,17,18 …”
Section: Discussionsupporting
confidence: 92%
“…We observed that lower individual-level education increased the mean levels of HbA 1c by 1.9% (95% CI 1.1, 2.8), independently of sex, age group, other individuallevel SES variables and area-level deprivation (social and material), which is in agreement with the few previous works. 13,17,18 To the best of our knowledge, there is a lack of research testing the competing models 'collective resources' versus 'local social inequality' for diabetes. Our study supports the collective resources model as we found that low municipality material deprivation is associated with better levels of HbA 1c after accounting for individual SES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these results are in line with previous studies showing that aggregated measures of socioeconomic status do improve the understanding of health outcomes compared to no socioeconomic information at all [11,12]. Using a similar methodological approach as the one used here, combining individual-level and neighbourhood-level official statistics, a Finnish study of patients with Diabetes type 2 found small-area based SES to be a relatively good substitute to individual-level information [23]. They found small-area based educational attainment to exhibit comparable predictive ability as individual educational attainment, while income did not have as consistent results between area-based and individual information.…”
Section: Discussionsupporting
confidence: 90%
“…The selected data were originally used for other research purposes and includes mainly patients with alcohol-use disorder (Rautiainen, Ryynänen, and Laatikainen 2018), type 2 diabetes (Toivakka et al 2018), coronary heart disease (Repo et al 2018) and anticoagulation (Leminen et al 2019). The data is therefore not an exact representation of the entire population, but its geographic distribution is rather similar, and it is useful for our study.…”
Section: Facility Location Optimisationmentioning
confidence: 99%